1993
DOI: 10.1164/ajrccm/147.3.535
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Ventilation and Gas Exchange during Airway Occlusion in the Normal Human Lung

Abstract: The effectiveness of collateral ventilation in maintaining alveolar gas tensions in obstructed lung segments was investigated using fiberoptic bronchoscopy to place an occluding catheter-tip balloon in selected lobar and segmental bronchi in supine normal human subjects. Gas tensions from beyond the occlusion were measured with a respiratory mass spectrometer. Collateral ventilation is known to be minimal between lobes; therefore, values measured in obstructed lobes provide a control. No significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
2
14
0
1
Order By: Relevance
“…The work of KIKUCHI et al [56] found surfactant blocked collateral pores but postulated these opened in the presence of lung pathology. This work was supported by MORELL et al [57] in 1993 who found that in normal lungs, 80% of the collateral pores are ®lled with surfactant and that they are indeed very small, in the order of 2.6 mm. It has been suggested that different channels provide collateral ventilation at different states of lung in¯ation and that the bronchoalveolar channels of Martin are the most important in collateral ventilation [56].…”
Section: Physiological Effectssupporting
confidence: 52%
“…The work of KIKUCHI et al [56] found surfactant blocked collateral pores but postulated these opened in the presence of lung pathology. This work was supported by MORELL et al [57] in 1993 who found that in normal lungs, 80% of the collateral pores are ®lled with surfactant and that they are indeed very small, in the order of 2.6 mm. It has been suggested that different channels provide collateral ventilation at different states of lung in¯ation and that the bronchoalveolar channels of Martin are the most important in collateral ventilation [56].…”
Section: Physiological Effectssupporting
confidence: 52%
“…We conclude that collateral ventilation occurs to a much greater extent in the emphysematous than in the normal lung and may be responsible for the relative preservation of gas exchange characteristic of this condition. Morrell Resistance to collateral flow of gas is known to be high in the normal human lung (1,2), and we previously confirmed directly that the contribution of intersegmental collateral ventilation to gas exchange in the normal lung is small (3). However, collateral resistance (Rcoll) may be lower than airway resistance in emphysematous lungs (4), and under these circumstances there may be a greater tendency for gas to flow by collateral channels into obstructed regions of lung.…”
supporting
confidence: 67%
“…As Cetti et al [6] pointed out, this may oversimplify the collateral ventilation. Alternatively, Morrell et al [29] proposed to measure collateral ventilation by occluding a lobe or segment with a balloon catheter under the guidance of a bronchoscope; however, their measurement showed the existence of collateral ventilation even for normal segment, suggesting the potential unreliability of this method. In particular, Sciurba et al analyzed both fissure integrity and emphysema heterogeneity as a surrogate for interlobar collaterals in their study [10].…”
Section: Discussionmentioning
confidence: 99%